PERKEMBANGAN PEMEROLEHAN BAHASA PADA ANAK: PERSPEKTIF ORGAN BICARA DAN SISTEM SARAF - Nisya Hanim; Silvina Noviyanti; Bella Rahmawati; Riska Mentari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Language acquisition in children is a biological, cognitive, and social process that develops from birth through early childhood. Each stage of language development is closely related to the maturation of speech organs, the development of the central nervous system, and the quality of environmental stimulation. This study aims to analyze the roles of speech organs and the nervous system in children’s language acquisition through direct observation. This research applied a descriptive qualitative approach using observation, interview, and documentation techniques. The results indicate that organs such as the tongue, lips, larynx, jaw, and resonance cavities undergo gradual development that strongly influences articulation and phonological abilities. The central nervous system including Broca’s area, Wernicke’s area, the cerebellum, and several cranial nerves plays a major role in coordinating speech production and comprehension. This study emphasizes that language acquisition is an integrated process shaped by biological readiness, neurological maturation, and environmental stimulation.